Screening oropharyngeal dysphagia in hospitalized older adults: A prevalent problem associated with mortality - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2017)
Objective: Oropharyngeal dysphagia (OD) is a common but underdiagnosed syndrome among older adults. The aim of this study was to assess the prevalence of OD in hospitalized older adults by using ten-item Eating Assessment Tool (EAT-10) and the relationship between mortality and OD. Patients and Methods: Patients aged over 65 years admitted to an internal medicine inpatient clinic of a university hospital in Turkey were enrolled in the study. The number of drugs, the number of chronic diseases, routes of feeding (oral, parenteral, or both), length of hospital stay, albumin levels on admission day, and mortality status of the patients were recorded by a physician. The EAT-10 questionnaire was administered to all patients for OD. Results: One hundred and thirty-six patients (54.4% female) were enrolled in the study. Their mean age was 74.6 +/- 6.6 years. The prevalence of OD in hospitalized older adults was 23%. The mortality rates were significantly higher in the dysphagic subjects as compared to the non-dysphagic ones (25.8% vs. 10.5%; p=0.041). The number of patients with malignancy was significantly higher in the dysphagic group as compared to the non-OD subjects (41.9% vs. 20%; p=0.018). Conclusion: OD is a geriatric syndrome and should be screened and treated in all geriatric patients in hospitals. It will improve patient outcomes and quality of life.
Keywords: Hospitalization; Older patients; Oropharyngeal dysphagia; Screening; Mortality